Motivational factors encouraging volunteerism among youths at the faculty of cognitive sciences and human development, Universiti Malaysia Sarawak (UNIMAS) / Hadri Yusuf and Nur Rauhah Kamarozzaman - Yusuf, Hadri; Kamarozzaman, Nur Rauhah (2018)
This chapter consists of several sections. Section 1.2 describes the background of study on volunteerism among youths. Section 1.3 highlights the problem statement of this research. Next, Section 1.4 discusses research objectives. Section 1.5 states the research questions meanwhile, Section 1.6 discusses research hypotheses. Section 1.7 discusses scope of research while Section 1.8 explains the significance of research. Section 1.9 provides the definitions for key terms. Section 1.10 describes the organization off research. Finally, Section 1.11 concludes this chapter with chapter summary.